Temporal Dynamics of Aerodynamic Canopy Height Derived From Eddy Covariance Momentum Flux Data Across North American Flux Networks. Issue 17 (6th September 2018) - Chu, Housen; Baldocchi, Dennis D.; Poindexter, Cristina; Abraha, Michael; Desai, Ankur R.; Bohrer, Gil; Arain, M. Altaf; Griffis, Timothy; Blanken, Peter D.; O'Halloran, Thomas L.; Thomas, R. Quinn; Zhang, Quan; et al.
Abstract: Aerodynamic canopy height ( h a ) is the effective height of vegetation canopy for its influence on atmospheric fluxes and is a key parameter of surface‐atmosphere coupling. However, methods to estimate h a from data are limited. This synthesis evaluates the applicability and robustness of the calculation of h a from eddy covariance momentum‐flux data. At 69 forest sites, annual h a robustly predicted site‐to‐site and year‐to‐year differences in canopy heights ( R 2 = 0.88, 111 site‐years). At 23 cropland/grassland sites, weekly h a successfully captured the dynamics of vegetation canopies over growing seasons ( R 2 > 0.70 in 74 site‐years). Our results demonstrate the potential of flux‐derived h a determination for tracking the seasonal, interannual, and/or decadal dynamics of vegetation canopies including growth, harvest, land use change, and disturbance. The large‐scale and time‐varying h a derived from flux networks worldwide provides a new benchmark for regional and global Earth system models and satellite remote sensing of canopy structure. Plain Language Summary: Vegetation canopy height is a key descriptor of the Earth surface and is in use by many modeling and conservation applications. However, large‐scale and time‐varying data of canopy heights are often unavailable. This synthesis evaluates the applicability and robustness of the calculation of canopy heights from the momentum flux data measured at eddy covariance flux tower sites (i.e., meteorological observation towers with high frequency measurements of wind speed and surface fluxes). We show that the aerodynamic estimation of annual canopy heights robustly predicts the site‐to‐site and year‐to‐year differences in canopy heights across a wide variety of forests. The weekly aerodynamic canopy heights successfully capture the dynamics of vegetation canopies over growing seasons at cropland and grassland sites. Our results demonstrate the potential of aerodynamic canopy heights for tracking the seasonal, interannual, and/or decadal dynamics of vegetation canopies including growth, harvest, land use change, and disturbance. Given the amount of data collected and the diversity of vegetation covered by the global networks of eddy covariance flux tower sites, the flux‐derived canopy height has great potential for providing a new benchmark for regional and global Earth system models and satellite remote sensing of canopy structure. Key Points: Aerodynamic canopy height can be calculated robustly and routinely from the eddy covariance momentum flux data Our estimates match well with in situ measurements of canopy heights across a wide variety of vegetation and ecosystem types Aerodynamic canopy height can be used to track the dynamics of vegetation canopies, including plant growth, harvest, and disturbance